Bateniâs Point of View in Simple and Compound Verbs in Farsi - مجید دادفر; حمیدرضا سلمانی (مطالعات زبانی و بلاغی)
Some of the Grammar ians and linguistic on the scientists believe that Farsi language lacks Compound verbs. Another group, other hand, denies this idea and say that Farsi does. So they discuss in the types of compound verbs and the ways of discriminating them. One of the most important points of view about these verbs is M.Reza Bateniâs idea. So in this paper, after reviewing these points of view, we discuss about simple verbs and their functions. Also, we consider these questions: are simple verbs a linguistic necessity or an obstacle in language? And, whether the meaning of simple and compound Verbs are same or not? It seems that applying simple verbs finally leads to foregrounding and de-familiarization of language. Based on this, these verbs differ in meaning, structure and functions.